Hire, Retain, and Grow Top Millennial Talent. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2016)
Learn why millennials are different, what they contribute to the workforce, and why retaining millennial talent is imperative to staying competitive.